Biosensing: Densely Packed Microgoblet Laser Pairs for Cross‐Referenced Biomolecular Detection (Adv. Sci. 10/2015). Issue 10 (October 2015) - Bog, Uwe; Brinkmann, Falko; Wondimu, Sentayehu Fetene; Wienhold, Tobias; Kraemmer, Sarah; Koos, Christian; Kalt, Heinz; Hirtz, Michael; Fuchs, Harald; Koeber, Sebastian; Mappes, Timo
<x xml:space="preserve">Abstract</x> In article 1500066, U. Bog, M. Hirtz, and co‐workers demonstrate on‐chip biomolecular sensing using whispering‐gallery‐mode microgoblet lasers. Biomolecular detection is usually affected by signal disturbances, induced by refractive index and temperature fluctuations inside the liquid analyte. The densely packed laser pairs enable mutual and localized filtering of such signal disturbances. The sensor functionalization is performed by aligned microcontact stamping, resulting in a highly localized, cross‐contamination‐free treatment of the individual microlasers.